Pengaruh Model Discovery Learning terhadap Kemampuan Pemecahan Masalah Matematis pada Materi Bilangan Bulat di Kelas VII Mts Negeri Karo - Yaumil Hasri; Ella Andhany; Ammamiarihta Ammamiarihta (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the effect and improvement of students’ mathematical problem-solving abilities through the implementation of the Discovery Learning model on integer material. The study employed a quantitative approach with a quasi-experimental design involving two groups, namely an experimental class receiving Discovery Learning and a control class receiving conventional instruction. Data were collected through problem-solving tests administered before and after the treatment. The data analysis focused on identifying differences in abilities and the level of improvement between the two groups. The results indicate that the Discovery Learning model has a significant effect on students’ mathematical problem-solving abilities compared to conventional learning. Furthermore, the improvement in the experimental class is categorized at a higher level than that of the control class. These findings suggest that Discovery Learning is effective in enhancing students’ problem-solving abilities and can be used as an alternative instructional model to promote active learning and deeper conceptual understanding.